2015
DOI: 10.1111/aor.12642
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Antithrombin Replacement Prior to Cardiopulmonary Bypass in Neonates

Abstract: Neonates have low levels of antithrombin. Inadequate anticoagulation during cardiopulmonary bypass (CPB) due to low antithrombin activity may result in a poor preservation of the coagulation system during bypass. We hypothesize that antithrombin replacement to neonates prior to CPB will preserve the hemostatic system and result in less postoperative bleeding. A randomized, double-blinded, placebo-controlled pilot study of antithrombin replacement to neonates prior to CPB was conducted. Preoperative antithrombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The decision to supplement AT to 100% was made based on the pediatric literature in nonsurgical pediatric patients with known AT deficiency and the few existing references to its use in CPB in children. [29][30][31][32] The optimal level of AT for adequate anticoagulation is unclear, and lower replacement targets may be reasonable and as effective. Conversely, because AT levels decrease significantly in the early postoperative period, replacement to higher levels intraoperatively 13 or re-dosing in the ICU might show additional benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to supplement AT to 100% was made based on the pediatric literature in nonsurgical pediatric patients with known AT deficiency and the few existing references to its use in CPB in children. [29][30][31][32] The optimal level of AT for adequate anticoagulation is unclear, and lower replacement targets may be reasonable and as effective. Conversely, because AT levels decrease significantly in the early postoperative period, replacement to higher levels intraoperatively 13 or re-dosing in the ICU might show additional benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials of preoperative antithrombin supplementation in adults undergoing cardiac surgery with the use of CPB have been published, and there has been one pilot study of antithrombin replacement in neonates undergoing CPB. 28,29 Antithrombin replacement currently is used in pediatric patients on extracorporeal life support, and its use has increased heparin efficacy and reduced dosing in these patients. 30…”
Section: Antithrombinmentioning
confidence: 99%
“…25,34,35 The Congenital Cardiac Anesthesia Society rFVIIa Task Force agrees on an initial dose of 90 mg/kg based on previous studies. 25 Future directions in the prevention and treatment of postbypass coagulopathy in the neonate include intense heparin management with antithrombin level monitoring and replacement 28,29,36 and the use of individualized anticoagulation management systems that have been shown to decrease blood product administration in infants undergoing cardiac surgery using CPB. 37 Although there is no evidence to support the use of newer factor concentrates such as 3-and 4-factor PCCs and fibrinogen concentrate in this population, 34 there is ex vivo evidence that 3-and 4-Factor PCC augments thrombin generation in neonatal plasma after CPB and may be a useful adjunct to standard blood component therapy.…”
Section: Postbypass Bleeding In Neonatesmentioning
confidence: 99%
“…4 Other small studies have shown that while AT replacement increases AT levels, it does not lead to less transfusion. 5 Prior to answering the question of whether we should supplement AT in neonates and infants undergoing cardiac surgery, the relationship between AT level and transfusion requirements should be investigated. Currently there is a paucity of data in whether AT deficiency preoperatively impacts transfusion requirements intra and post-operatively.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized controlled study involving 40 patients, Joost, et al showed that AT supplementation led to fewer donor exposures and chest tube output but not significantly different transfusion volumes 4 . Other small studies have shown that while AT replacement increases AT levels, it does not lead to less transfusion 5 . Prior to answering the question of whether we should supplement AT in neonates and infants undergoing cardiac surgery, the relationship between AT level and transfusion requirements should be investigated.…”
Section: Introductionmentioning
confidence: 99%